(untitled) (Revista Electrónica REDINE, 2018)
The following investigation has as a main purpose to show the Artkidz project, which is based on the Theory of Multiple Intelligences. This investigation pretends to develop the linguistic and creative potential in kids from 4 to 12 ages who belong to the Artkidz program, taking place in the Museum of Barquisimeto. This one is a camp investigation, corresponding to a special project, which starts from a diagnostic study of educative needs in a group of children from the Centro-Occidental region. Besides, this project will be used as a basis to support the design of a didactic program that will allow us develop the Multiple Intelligences in kids from Lara State. For this reason, a didactic activities control will be established, also will be planned the possible evaluations, both qualitative and quantitative. This will allow us have the control of each student’s performance during the execution of the project.